Thermal dose dependent optical property changes of ex vivo chicken breast tissues between 500 and 1100 nm - Adams, M; Wang, Q; Cleveland, R; Roy, R (IOP Publishing, 2014)
This study examines the effectiveness of the thermal dose model in accurately predicting thermally induced optical property changes of ex vivo chicken breast between 500–1100 nm. The absorption coefficient, μa, and the reduced scattering coefficient, $μ _s^′$, of samples are measured as a function of thermal dose over the range 50 °C–70 °C. Additionally, the maximum observable changes in μa and $μ _s^′$ are measured as a function of temperature in the range 50 °C–90 °C. Results show that the standard thermal dose model used in the majority of high-intensity focused ultrasound (HIFU) treatments is insufficient for modeling optical property changes, but that the isodose constant may be modified in order to better predict thermally induced changes. Additionally, results are presented that show a temperature dependence on changes in the two coefficients, with an apparent threshold effect occurring between 65 °C–70 °C.